2021
DOI: 10.1111/acem.14204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prehospital workflow optimization on treatment delays and clinical outcomes in acute ischemic stroke: A systematic review and meta‐analysis

Abstract: Background The prehospital phase is critical in ensuring that stroke treatment is delivered quickly and is a major source of time delay. This study sought to identify and examine prehospital stroke workflow optimizations (PSWOs) and their impact on improving health systems, reperfusion rates, treatment delays, and clinical outcomes. Methods The authors conducted a systematic literature review and meta‐analysis by extracting data from several research databases (PubMed, Cochrane, Medline, and Embase) published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 51 publications
(60 reference statements)
0
35
0
2
Order By: Relevance
“…System-based approaches have improved in-hospital temporal parameters, maximized the utility of reperfusion therapies, and improved clinical benefits to patients (46). Several studies on prehospital stroke workflow optimization (PSWO) have implemented various strategies and shown success in reducing workflow time delays and patient treatment rates (47). Chowdhury et al showed that improved IVT triage is significantly associated with improved rates of IVT and thus can increase the number of potential IVT candidates.…”
Section: Discussionmentioning
confidence: 99%
“…System-based approaches have improved in-hospital temporal parameters, maximized the utility of reperfusion therapies, and improved clinical benefits to patients (46). Several studies on prehospital stroke workflow optimization (PSWO) have implemented various strategies and shown success in reducing workflow time delays and patient treatment rates (47). Chowdhury et al showed that improved IVT triage is significantly associated with improved rates of IVT and thus can increase the number of potential IVT candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Our results nevertheless confirm that systems interventions improve time savings in the in‐hospital AIS workflow, meeting the aim of our study. Although our meta‐analysis focussed upon in‐hospital systems interventions, pre‐hospital systems interventions are also critical to AIS workflow, in reducing treatment times 13 …”
Section: Discussionmentioning
confidence: 99%
“…Despite several studies demonstrating efficacy in reducing treatment delay, it is yet to be determined if the benefits of systems interventions or workflow optimizations in the in‐hospital settings remain consistent in systematic review and meta‐analysis of pooled studies. Our recent study demonstrated that pre‐hospital stroke workflow optimization significantly improves reperfusion treatment‐related time metrics leading to improvement in IVT reperfusion rates 13 . The current study sought to examine the effect of in‐hospital system‐level optimization or systems‐based interventions on treatment delays, reperfusion rates within 1 hour of presentation to the Emergency Department (ED) and clinical outcomes in AIS patients treated with reperfusion therapy by performing a systematic review and meta‐analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Prehospital pathways are critical to acute stroke organisation. Systems-level approaches to improving the process of care or prehospital acute stroke pathways have gained attention over the last decade [1][2][3][4]. The underlying principle is based on the fact that stroke systems of care, being a timecritical medical emergency, would benefit from streamlining the process of care or pathways by reducing time delays [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies aimed at improving the prehospital system are promising and demonstrate the value of such approaches [5]. However, it is yet to be established if the process improvements due to these interventions translate to the clinical benefit of stroke patients [3]. This article will provide an overview of current systems of acute stroke care with a focus on prehospital pathways and identify opportunities for improvement.…”
Section: Introductionmentioning
confidence: 99%